VARIATIVITY PRINCIPLE IN MUSICAL TRAINING AT THE UNIVERSITIES OF MUSIC PROFILE - Veronika S. Korina (Высшее образование в России)
This article considers the author’s understanding of solution the problem of variative bachelors’ training. Variation isconsidered as a principle of organizing structure and content of training process on different stages of education system. The individual students’ itineraries and individual educational modules are designed on the base of variative approach. The author represent the conception of variative education in the sphereof music. The structure of educational process is considered as the complex of universal and variative units. It allows to form the unique content of individual itineraries and educational modules, taking into account peculiarities of courses and training profiles.